Changes in the Thickness of Different Retinal Layers Following Intravitreal Injection of Bevacizumab in Patients with Diabetic Macular Edema and Its Association with post Treatment Vision - Nikkhah, Homayoun; Valipoor, Masoome; Ramezani, Alireza; Karimi, Saeed; Entezari, Morteza; Hatami, Mohammad Mehdi; Shojaei, Ahmad (Journal of Ophthalmic and Optometric Sciences, 2024)
Purpose: To investigate changes in the thickness of different retinal layers following intravitreal injection of bevacizumab in patients with diabetic macular edema (DME) and its association with post treatment vision. Patients and Methods: Bevacizumab injection was administered three times, four weeks apart. Study of retinal layer segmentation was performed manually only at the beginning of the study and at the final examination (month 6) using the SD-OCT imaging and retinal thickness was recorded in the 1, 3, and 6 mm areas of the central macula and in different quadrants. Results: A total of 29 eyes from 29 patients were included in the study. The mean retinal thickness in the central macular area decreased from 409 ± 72 microns at the beginning of the study to 315 ± 44 microns at month six (P < 0.001). In the inner ring, the retinal thickness decreased from 410 ± 44 microns to 359 ± 25 microns (P < 0.001). These values in the outer ring were 342 ± 42 microns and 320 ± 31 microns, respectively (P < 0.001).The reduction in thickness in certain retinal layers of the inner and outer retina, along with better baseline visual acuity (P < 0.001) were positively associated with final visual acuity. Conclusion: Our study showed that the changes in retinal thickness after intravitreal injection of bevacizumab occurs in both the inner and outer retina, and the reduction in thickness in certain retinal layers along with better baseline visual acuity is positively associated with final visual acuity.